CSF Alzheimer's disease-like pattern in corticobasal syndrome: evidence for a distinct disorder. Issue 8 (22nd February 2011) - Borroni, Barbara; Premi, Enrico; Agosti, Chiara; Alberici, Antonella; Cerini, Carlo; Archetti, Silvana; Lanari, Alessia; Paghera, Barbara; Lucchini, Silvia; Caimi, Luigi; Padovani, Alessandro
Abstract : Background: Corticobasal syndrome (CBS) has a heterogeneous neuropathological spectrum, ranging from the classical corticobasal degeneration to Alzheimer's disease (AD). The neuropathology of CBS is still unpredictable. CSF tau/abeta ratio is a reliable marker of AD. Objective: To evaluate the presence of a distinct clinical and neuroimaging CBS phenotype according to CSF pattern. Methods: 30 patients fulfilling current clinical criteria for CBS entered the study. Each patient underwent a clinical and standardised neuropsychological assessment, and CSF analysis (total tau and abeta42 dosages). CSF AD-like pattern and CSF non-AD like pattern (nAD-like) were identified. In 23 CBS cases, 99m Tc-ECD single photon emission computed tomography (SPECT) scan was performed and analysed by statistical parametric mapping. Results: CSF AD-like pattern was reported in six cases (20%). The two subgroups did not differ in demographic characteristics or global cognitive impairment. The AD-like group showed greater impairment of memory performances, language and psychomotor speed while the nAD-like group had more severe extrapyramidal syndrome with comparable apraxia scores. Voxel by voxel analysis on SPECT images demonstrated that CBS AD-like patients had greater hypoperfusion in the brain areas typically affected by AD—namely, precuneus, posterior cingulate and hippocampus, bilaterally—compared with nAD-like patients (p<0.001). No clusters above the pre-established threshold were detected when nAD-like were compared with AD-like patients. Conclusions: CSF AD-like profile in CBS is associated with earlier memory impairment and brain abnormalities typically found in classical AD. These findings argue for the usefulness of CSF testing to identify AD in CBS, and might suggest a different pharmacological approach on the basis of biological data.